2015
DOI: 10.1097/bsd.0b013e3182aab2ff
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Spinal Balance in Adult Spine Deformity Patients With Long Spinal Fusions

Abstract: After surgical correction of spinal deformities, coronal spinal decompensation appears in an increased number of patients at last follow-up postoperatively but without significant differences in coronal plane C7PL during the postoperative period. Attention should be paid to patients with osteoporosis and those with a combination of previous same site posterior spine surgery and new anterior approach surgery for changes of coronal balance postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…There is a growing body of literature correlating coronal imbalance with a negative effect on patient outcomes. 4 , 11 , 12 , 21 Pluomis et al 12 showed that patients with coronal imbalance, defined as >5 cm in their study, showed a negative correlation with both mental health, vitality and physical function scores. In a large retrospective analysis, Koller et al 11 determined that patients with coronal imbalance at follow-up had poorer clinical outcomes following deformity correction.…”
Section: Discussionmentioning
confidence: 88%
“…There is a growing body of literature correlating coronal imbalance with a negative effect on patient outcomes. 4 , 11 , 12 , 21 Pluomis et al 12 showed that patients with coronal imbalance, defined as >5 cm in their study, showed a negative correlation with both mental health, vitality and physical function scores. In a large retrospective analysis, Koller et al 11 determined that patients with coronal imbalance at follow-up had poorer clinical outcomes following deformity correction.…”
Section: Discussionmentioning
confidence: 88%
“…Bao et al [3] have found that patients with preoperative convex CM are at higher risk of postoperative persistence or worsening of CM. Ploumis et al [20] in a retrospective analysis of 54 patients followed-up for 2-5 years after long fusions for ASD found that while sagittal malalignment was consistently reduced by surgery, the prevalence of CM did not change from the preoperative to the early postoperative period. In nearly 60% of the cases, preoperative CM was not corrected by surgery, and nearly 9% of patients without preoperative CM showed new onset Postoperative convex coronal malalignment has been described after fusions with the lowest instrumented vertebra (LIV) at L5 for lumbar scoliosis with the use of transpsoas lateral cages, and the likely mechanism is overcorrection of the main lumbar curve over a stiff L5-S1 segment that cannot correct spontaneously to achieve a horizontal takeoff [21].…”
Section: Discussionmentioning
confidence: 98%
“…However, due to the complexity of the structural pathologies of DLS, it might be challenging to achieve satisfactory correction for each DLS patient, resulting in postoperative coronal imbalance. As reported in the literature, the prevalence of postoperative coronal imbalance in adult scoliosis patients ranged from 25.6 to 31.6% 2,3 . In addition, coronal imbalance may also have negative impact on health-related quality of life 2,4 .…”
Section: Level Of Evidencementioning
confidence: 89%